The Influence Of Work-Life Balance And Job Satisfaction On Employee Performance At Pt. Bank Sulselbar - Agung Widhi Kurniawan; Nurhaedah; Khaidir Syahrul; Febriansyah Yoga Pratama (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study aims to analyze the influence of work-life balance and job satisfaction on employee performance at PT. Bank Sulselbar. The research is grounded in the view that, in an era of digital transformation and increasing performance demands, employees’ ability to harmonize work and personal roles, as well as their satisfaction with various aspects of their job, is crucial for maintaining optimal performance. A quantitative verificative approach was employed with a sample of 52 employees selected using accidental sampling from a total population of 514 staff. Data were collected through structured questionnaires using a five-point Likert scale and supported by documentation of company records. The variables examined include work-life balance and job satisfaction as independent variables, and employee performance as the dependent variable. Data analysis involved validity and reliability testing, classical assumption tests, and multiple linear regression, complemented by t-tests and F-tests at a 5% significance level. The results show that work-life balance has a positive and significant effect on employee performance, indicating that employees who experience better balance between work and personal life tend to demonstrate higher productivity and work quality. Job satisfaction also has a positive and significant effect on employee performance, suggesting that satisfied employees are more motivated, committed, and engaged in their tasks. Simultaneously, work-life balance and job satisfaction explain 47.8% of the variance in employee performance, while the remaining 52.2% is influenced by other factors not examined in this study. These findings underscore the strategic importance of designing human resource policies that support employee well-being and satisfaction to enhance organizational performance.